Hubungan Pola Asuh Orangtua dengan Capaian Dimensi Mandiri Profil Pelajar Pancasila pada Anak Usia Dini - Afiani, Ardita; Rahman, Taopik; Purwati, Purwati (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Character development in early childhood, particularly in the dimension of independence, is a critical aspect of shaping the Profil Pelajar Pancasila (Pancasila Student Profile). However, studies examining the relationship between parenting styles and the development of independent character in young children remain limited. This study aims to analyze the correlation between parenting styles and the independence dimension of early childhood development. Using a quantitative correlational approach, data were collected from 92 parents in Cipedes District through standardized and validated questionnaires measuring parenting styles and children's independence outcomes. The data were analyzed using Spearman’s correlation test. The results show a significant positive relationship between parenting style and child independence (r = 0.590, p < 0.001). The majority of respondents (89.1%) applied a democratic parenting style, and 90.2% of children were categorized as